Saperi condivisi, saperi in conflitto: Etnografia dell’apicoltura in Sardegna - Meloni, Greca N. (Antropologia Pubblica, 2019)
The paper analyzes the outcomes of the processes of sharing and integration between anthropological knowledge and expertise in the field of beekeeping in Sardinia. The research inserts as a part of the ongoing debate that sees a large part of the community of Sardinian beekeepers opposed to the regional government agencies accused of formulating plans for environmental and landscape management that do not consider the forage potential of the territory, compromising the beekeeping sector. The research offers the opportunity of investigating the processes of negotiation and construction of identity activated by the use of a camcorder within the ethnographic research. Through the analysis of some practical cases, the article intends of showing how the anthropological skills and knowledge lead the researcher to take on the role of “cultural mediator” between the rights claimed by the beekeepers’ community and the reasons of the institutions, the former partially articulated in informal local knowledge based on direct contact with the “natural world”, the latter developed in the field of technical-scientific knowledge. Furthermore, the research questions the possible applications of the anthropological research outside the academic field activity exploring the disclosure activity taken on by the anthropologist through the blog Abieris e Abis. Finally, the paper introduces the concept of co-management of natural resources, investigating possible forms of interdisciplinary collaboration and modalities of mutual recognition of formal and informal knowledge.